2017
DOI: 10.1159/000477631
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Imaging: A Novel Tool for Detecting Carotid Artery Thrombosis in Mice

Abstract: Thrombosis is a main cause of acute cardiovascular events, and detecting thrombi in small arteries via noninvasive imaging remains challenging. In this study, we employed a novel imaging method, photoacoustic imaging (PAI), to study thrombosis in a mouse model of ferric chloride (FeCl3)-induced arterial thrombosis and compared the ability of this method to detect thrombosis with that of a conventional imaging method, namely, ultrasound. The mice (n = 20) were divided equally into the following 4 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Two or three drops of saline were applied to the vessel to avoid drying up. A piece of filter paper saturated with 20% (w/v) FeCl 3 solution was placed on the artery and incubated for 3 min (Liang et al, 2015b ; Li et al, 2017 ). After incubation the artery was rinsed with saline.…”
Section: Methodsmentioning
confidence: 99%
“…Two or three drops of saline were applied to the vessel to avoid drying up. A piece of filter paper saturated with 20% (w/v) FeCl 3 solution was placed on the artery and incubated for 3 min (Liang et al, 2015b ; Li et al, 2017 ). After incubation the artery was rinsed with saline.…”
Section: Methodsmentioning
confidence: 99%
“…In (38), OA was employed to detect thrombosis of the carotid artery in a corresponding animal model (Figure 4A). Carotid artery thrombosis was induced by an iatrogenic chemical injury via the application of a filter paper soaked with 20% FeCl 3 around the vessel wall after the surgical exposure of the carotid artery.…”
Section: Small Animal Modelsmentioning
confidence: 99%
“…The white arrows indicate the locations of the thrombi in the FeCl3-treated mice. Adapted with permission from(38). (B) Optoacoustic (1,064 nm)-ultrasound overlays of the carotid arteries/plaques of a mouse before (up) and 24 h after (middle and down) the intravenous injection of a molecular probe (PBD-CD36 NP) targeting inflammation.…”
mentioning
confidence: 99%
“…By measuring the optical absorption of hemoglobin, Li et al reported the detection of artery thrombosis in mice. 134 Red blood cells (RBCs) in fresh clot formation generate higher PA signal than old clots. As the clot ages, it retracts forcing RBCs and other content out of the clot 135 resulting in a reduced PA signal.…”
Section: Vascular Imagingmentioning
confidence: 99%